Effect of dips in a 1-methylcyclopropene-generating solution on 'Harrow Sun' plums stored under different temperature regimes - Vicente, Ariel Roberto; Crisosto, Carlos H.; Manganaris, George A. (My University, 2007)
The effect of postharvest dips in a 1-methylcyclopropene-generating solution of the formulation AFxRD-038 (Rohm & Haas) on plum fruit (Prunus salicina Lindell cv. 'Harrow Sun') quality and ripening during storage was determined. Fruit weight loss, tissue firmness, soluble solids content (SSC), titratable acidity (TA), ethylene production, respiration, and the activities of the cell wall modifying enzymes polygalacturonase (PG), 1,4-β-D-glucanase/ glucosidase (EGase), β-galactosidase (β-gal), and pectin methylesterase (PME) were measured. Fruit reddening, anthocyanin content, and phenylalanine ammonia-lyase (PAL) activity were also analyzed. The 1-MCP-treated fruit showed reduced ethylene production and respiration rate and delayed softening, which was associated with the reduction in the activity of PG, EGase, and β-gal. The immersion in 1-MCP-generating solutions also decreased weight and acidity loss without modifying the fruit SSC. The immersion treatment was particularly effective in the fruit stored at 5°C, keeping higher overall quality, maintaining lower levels of anthocyanins and PAL activity, and preventing flesh reddening. The present data show that beneficial effects in delaying plum fruit ripening and controlling chilling injury can be obtained by dipping the fruits in a solution of this novel 1-MCP-generating formulation
Keywords: Plum; Fruit--Ripening; Biosynthesis; Chemistry; Enzymology; Food--Preservation; Prunus; Ethylene